Does heavy-tailedness matter in regime shifts and persistence in volatility estimation? Evidence from six GCC economies - Ajab A. Alfreedi; Zaidi Isa; Abu Hassan (Journal of Statistical and Econometric Methods, 2012)
This study examines the regime shifts in volatility in the stock markets of Gulf Cooperation Council (GCC) countries by employing the iterated cumulative sum of squares generalized autoregressive conditional heteroscedasticity (ICSSGARCH) model. Using the weekly data over the period 2003-2010, the GARCH models are estimated accounting for the sudden shifts detected by ICSS algorithm. The unexpected changes in stock price volatility seem to arise from the important global, regional, and domestic political as well as economic events. The findings also suggest that the ignorance of structural changes in volatility seems to lead to overestimation of persistence parameters of GARCH models. This finding corroborates many earlier studies in this context.
Keywords: 330; GCC; stock market volatility; ICSS-GARCH; heavy-tailed conditional density